2012
DOI: 10.1371/journal.pone.0033032
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Protects Mice from Community-Associated Methicillin-Resistant Staphylococcus aureus Pneumonia

Abstract: Background α-toxin is one of the major virulence factors secreted by most Staphylococcus aureus strains, which played a central role in the pathogenesis of S. aureus pneumonia. The aim of this study was to investigate the impact of capsaicin on the production of α-toxin by community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) strain USA 300 and to further assess its performance in the treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…The hemolytic activity of the culture supernatant was determined as described in our previous study [11]. Briefly, S. aureus strains were cultured (37°C, 200 rpm) in TSB supplemented with the indicated concentrations of isorhamnetin and centrifuged at 10,000 ×g for 5 min at the post-exponential phase (OD 600 of 2.5).…”
Section: Determination Of Hemolytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The hemolytic activity of the culture supernatant was determined as described in our previous study [11]. Briefly, S. aureus strains were cultured (37°C, 200 rpm) in TSB supplemented with the indicated concentrations of isorhamnetin and centrifuged at 10,000 ×g for 5 min at the post-exponential phase (OD 600 of 2.5).…”
Section: Determination Of Hemolytic Activitymentioning
confidence: 99%
“…The role of Hla in the pathogenesis of S. aureus is critical, as evident from the fact that mutants lacking Hla display reduced virulence in many animal models of diseases [1,8,13,19]. Some natural compounds identified in our laboratory can attenuate the virulence of S. aureus by inhibiting the expression or antagonizing the pore-forming activity of Hla [11,17,21]. Thus, this protein is a potential target for the development of anti-virulence agents against S. aureus infections.…”
Section: Introductionmentioning
confidence: 99%
“…It is a naturally occurring phytochemical and is one of the active ingredients of red and chili peppers [1,2]. Peppers have become a popular culinary spice for food throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al reported that a treatment with subinhibitory concentrations of thymol or eugenol decreased the production of α-haemolysin and staphylococcal enterotoxins A and B in both methicillin-sensitive and methicillin-resistant S. aureus isolates [70,118]. Similar results have been obtained that demonstrate reduced S. aureus haemolysis activity and a decrease or even inhibition of the production of staphylococcal α-haemolysin after the treatment of allicin [119], alkaloid capsaicin [120], flavonoids farrerol [121], or epicatechin gallate [122]. Allicin, the major biologically active component of garlic, was shown to effectively neutralize the toxin pneumolysin-a main virulence factor that is produced by S. pneumoniae [123].…”
Section: Attenuating the Bacterial Virulencementioning
confidence: 63%